Dragon teeth [compact disc, unabridged] : a novel - Crichton, Michael, 1942-2008 (Harper Audio, 2017)
A tale set in the Wild West during the golden age of fossil hunting follows the exploits of two ambitious paleontologists who sabotage each others' careers in a rivalry that came to be known as the Bone Wars.